Analisis Penggunaan Media Sosial Sebagai Alat Komunikasi Pemasaran dalam Meningkatkan Brand Awareness: Studi Kasus pada UKM Vebcake Tulungagung - Anggraini, Fia Tri; Habib, Muhammad Alhada Fuadilah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Social media has now become something that is embedded in people's lives. In this digital era, social media users have increased a lot, so to gain effectiveness in marketing communications, Vebcake chooses to use social media. Through this strategy, Vebcake is able to increase brand awareness of its business. Marketing communications itself plays an important role in increasing brand awareness. Vebcake is a business operating in the bakery sector in Tulungagung that is well known to the public. This can be seen through Vebcake's social media, which has tens of thousands of followers and sales turnover which increases every year. Based on previous research, Vebcake already has good brand awareness. Consumers have a good perception of the Vebcake Brand and say that the products from the Vebcake Brand are delicious and high quality at an affordable price. This research aims to describe the implementation of marketing communications via social media carried out by Vebcake to increase brand awareness. This research uses a qualitative approach with a descriptive type. The results of this research found that Vebcake implements a marketing communication mix regularly so that the public can be aware of the existence of the Vebcake Brand. The marketing communication mix carried out is in the form of advertising, sales promotion, public relations and publicity, online marketing and social media, mobile marketing, direct and database marketing, and personal selling. The obstacles that Vebcake faced while carrying out this marketing communication were the problem of miscommunication and the communication device (smartphone) which was damaged. Keywords: brand awareness; marketing communications; social media